Bromoalkyl ATRP initiator activation by inorganic salts: experiments and computations. Issue 19 (1st April 2019) - Wang, Jirong; Han, Jianyu; Peng, Haiyan; Tang, Xiangying; Zhu, Jintao; Liao, Rong-Zhen; Xie, Xiaolin; Xue, Zhigang; Fliedel, Christophe; Poli, Rinaldo
Abstract : The bromoalkyl ATRP initiator EBrPA is activated by many alkali, alkaline-earth and ammonium salts, leading to MMA polymerization, but only the iodides yield a controlled process because of a degenerative transfer mechanism contribution. Abstract : Ethyl α-bromophenylacetate (EBrPA) is able to initiate the bulk radical polymerisation of methyl methacrylate (MMA) under thermal conditions (90 °C) in the presence of a variety of simple alkali or alkaline-earth metal or n Bu4 N salts (Mt + X − with X − = chloride, bromide, iodide, carbonate, bicarbonate, sulfate, bisulfate, nitrate, hydroxide and hexafluorophosphate). Chain growth is controlled only when using iodide salts, which also gives one of the highest polymerisation rates. Using a substoichiometric amount of LiI as an activator, the polymerisation rate is unaffected by the LiI/initiator ratio when the initiator is cyanoisopropyl iodide (CPI) but increases with the activator amount when using EBrPA. Analysis of these rates in combination with the polymer molecular weights revealed a LiBr-catalysed halogen exchange between more active PMMA-I and less active PMMA-Br chains. In combination with a computational investigation by DFT methods, these findings demonstrate that while the rate of polymerisation is determined by the atom transfer equilibrium from EBrPA to the Mt + X − catalyst to yield EPA˙ and Mt + (BrX˙) −, controlled chain growth cannot be ensured exclusively by the persistent radical effect.